Multi-objective Function Optimization for Locating and Sizing of Renewable Energy Sources and Energy Storages in Radial Distribution Networks with Digital Directional Overcurrent Relays and Digital Dual-setting Directional Overcurrent Relays - Rezaei, Maryam Faghihi; Gandomkar, Majid; Nikoukar, Javad (Journal of electrical engineering & technology, 2022)
The purpose of distributed generation (DG), unlike centralized electricity generation, is to generate small-scale electrical energy as near as possible to load centers. The optimal size and location of distributed generation sources is important in the installation of these sources to improve the technical parameters of the network, including losses, voltage profile and short circuit levels. By connecting the DG to the distribution network, the protection coordination between the protective devices is lost. To solve this problem, in this paper, a new protection coordination scheme is proposed, using directional overcurrent relays (DOCRs) and digital dual-setting directional overcurrent relays (DS-DOCRs) in the distribution network in the presence of renewable energy sources (RESs) and energy storage system (ESSs). For this purpose, a multi-stage objective function is used. In the first stage, a weighted objective function is used to optimize the size and location of the RESs in order to reduce the cost of losses, reduce the cost of increasing and decreasing the voltage, and reduce the cost of installing RESs and ESSs. In the second stage, DOCR and DS-DOCR settings optimization, which includes A and B parameters in addition to pickup current (Ip) and time dial setting (TDS) parameters, is used to restore the lost protection coordination for the minimum fault current to the maximum fault current in the shortest possible time. The simulation results on the IEEE 33-bus network in the presence of RESs, using Analytical Hierarchy Process method (AHP) and genetic algorithm (GA) and DPL programming language in DIgSILENT software, show that the total operating time of digital relays, losses and network cost are reduced, and voltage profile is significantly improved.